Socialism national or international - "Borkenau, Franz" (London, 1942)
Dr. Borkenau discusses the ideals of international socialism in the light of the realities of a world of strife and struggle. He maintains that socialist internationalism of the old type has little relation to the problems of the present. The world has become much more nationalist, and the labour movements of all countries have had to give in to the forces of nationalism. He is sceptical of the revival of liberal-democratic internationalism in the League, and the attempt to revive the League in the shape of a Federal Union. He believes however, that powerful forces are working in the direction of the growth of supernational units, and points to symptoms of an impending sudden collapse of nationalism which would enable Labour to put itself at the head of an Anglo-American peace similar to the Roman piece which for centuries gave quiet and prosperity to the world.
Keywords: Political sceince